National Study of Pain Medicine Access Among Māori and Non-Māori Patients With Lung Cancer in New Zealand. (August 2021) - Gurney, Jason K.; Stanley, James; Adler, Jonathan; McLeod, Heather; Atkinson, June; Sarfati, Diana
Abstract : PURPOSE: Pain is among the most common and consequential symptoms of cancer, particularly in the context of lung cancer. Māori have extremely high rates of lung cancer, and there is evidence that Māori patients with lung cancer are less likely to receive curative treatment and more likely to receive palliative treatment and to wait longer for their treatment than non-Māori New Zealanders. The extent to which Māori patients with lung cancer are also less likely to have access to pain medicines as part of their supportive care remains unclear. METHODS: Using national-level Cancer Registry and linked health records, we describe access to subsidized pain medicines among patients with lung cancer diagnosed over the decade spanning 2007-2016 and compare access between Māori and non-Māori patients. Descriptive and logistic regression methods were used to compare access between ethnic groups. RESULTS: We observed that the majority of patients with lung cancer are accessing some form of pain medicine and there do not appear to be strong differences between Māori and non-Māori in terms of overall access or the type of pain medicine dispensed. However, Māori patients appeared more likely than non-Māori to first access pain medicines within 2 weeks before their death and commensurately less likely to access them more than 24 weeks before death. CONCLUSION: Given the plausibility that there are differences in first access to pain medicines (particularly opioid medicines) among Māori approaching end of life, further investigation of the factors contributing to this disparity is required.